Pengaruh Kepercayaan, Pengalaman Berbelanja, Penilaian Konsumen dan Kemudahan Penggunaan Aplikasi Belanja Online Lazada terhadap Keputusan Pembelian pada Mahasiswa Fakultas Ekonomi dan Bisnis Angkatan 2017 Universitas Muhammadiyah Metro - Larassati, Anindia; Siswoyo, Slamet Tedy (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study aims to analyze the effect of trust, shopping experience, consumer assessment, and the ease of use of the Lazada online shopping application on purchasing decisions. This type of research is a quantitative study with a population of 225 students using the Lazada application, only 145 samples were used according to predetermined criteria. The data used is secondary data distribution of questionnaires in the form of a list of questions with several alternative answers for respondents. The statistical test used to test the hypothesis is multiple linear regression analysis and is tested using the statistical packages for the social science (SPSS) program version 20. Based on the results of statistical tests, it shows that Trust, Shopping Experience, Consumer Assessment, and Ease of Use of the Lazada Online Shopping Application have a positive and significant effect on Purchasing Decisions.